2008
DOI: 10.1007/s00221-008-1523-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microgravity on gene expression in mouse brain

Abstract: Changes in gravitational force such as that experienced by astronauts during space flight induce a redistribution of fluids from the caudad to the cephalad portion of the body together with an elimination of normal head-to-foot hydrostatic pressure gradients. To assess brain gene profile changes associated with microgravity and fluid shift, a large-scale analysis of mRNA expression levels was performed in the brains of 2-week control and hindlimb-unloaded (HU) mice using cDNA microarrays. Although to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 73 publications
1
39
1
1
Order By: Relevance
“…Previous studies using traditional 2DE coupled with MALDI‐TOF have shown that 7 days SM induces the down‐regulation of structural and metabolic proteins . Other studies using microarray analysis reported that 14 days of SM induced changes in synaptic genes . Our previous study showed that SM decreases SNARE‐related proteins in the hippocampus, leading to impaired learning and memory function.…”
Section: Introductionmentioning
confidence: 70%
“…Previous studies using traditional 2DE coupled with MALDI‐TOF have shown that 7 days SM induces the down‐regulation of structural and metabolic proteins . Other studies using microarray analysis reported that 14 days of SM induced changes in synaptic genes . Our previous study showed that SM decreases SNARE‐related proteins in the hippocampus, leading to impaired learning and memory function.…”
Section: Introductionmentioning
confidence: 70%
“…It is possible that the observed impairment of neurogenesis in microgravity‐exposed embryos could be ascribed more to an impairment of the progenitor/neural cell migration than to the intrinsic cell neural differentiation. Interestingly, cDNA microarray showed that hindlimb‐unloading treatment up‐regulated key steps of synaptic plasticity and learning process in mouse brain [Frigeri et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Frigeri et al examined gene expression in mouse brain after 2 weeks hindlimb supesension (Frigeri et al 2008). Using 27K cDNA microarrays, they found 592 statistically significant genes with 1.5 fold or higher differential regulation.…”
Section: Microarray Analysis Of Microgravity Exposed Other Cellsmentioning
confidence: 99%